Students’ Perceptions of Wayground Use and Their Learning Performance in Bahasa Indonesia Course: A Correlational Study - Sri Rejeki; Angela Bayu Pertama Sari; Nur Amalia Solikhah; Cindyra Galuhwardani (ITScience (Information Technology and Science), 2025)
This study investigates the relationship between students’ perceptions of using Wayground, a gamified digital quiz platform, and their learning performance in a Bahasa Indonesia course. Wayground is designed to provide an interactive and engaging assessment experience in digital learning environments. Understanding how students perceive this platform and whether such perceptions influence their academic outcomes is essential for evaluating its effectiveness in higher education settings. This research employed a quantitative correlational design involving 84 students from Universitas Bina Sarana Informatika across three campuses: BSD, Tasikmalaya, and Tegal. Data were collected using a Technology Acceptance Model (TAM)-based questionnaire consisting of five constructs: perceived usefulness, perceived ease of use, engagement, clarity, and attitude. Students’ Wayground quiz scores were also collected. The data were analyzed using descriptive statistics, normality tests, and Pearson–Spearman correlation analyses. The findings show that students had highly positive perceptions of Wayground, with mean scores ranging from 3.67 to 3.90. They viewed the platform as interactive, user-friendly, and effective for digital evaluation. However, correlation analyses revealed no significant relationship between students’ perceptions and their quiz performance (p > 0.05). These results indicate that although students appreciated the platform, positive perceptions did not translate into higher learning outcomes. The study concludes that Wayground successfully enhances engagement and digital interactivity in learning environments. Nevertheless, positive perceptions alone are insufficient to guarantee improved academic performance. Achieving optimal learning outcomes may require additional factors such as learner motivation, adequate preparation, and effective instructional design.